Morphological characterization and genetic diversity based on the melon root system (Bioscience Journal, 2025)
Studies on plant root system architecture may yield valuable data for genetic improvement programs for developing cultivars that acquire water and nutrients more efficiently. This study used morphological descriptors to characterize the root system and evaluate genetic diversity among 30 melon accessions. A completely randomized experiment was conducted with 30 treatments and 5 replications. The plot consisted of one seedling. After seed germination, five seedlings were fixed in a dried growth medium for 12 days. Then, they were scanned and measured for primary root length and primary root neck diameter. Root hairs were visually evaluated. Finally, basal root angles were measured. The accessions diverged genetically regarding the root system morphological characteristics. The primary root neck diameter contributed the most to the dissimilarity between the accessions (43.06%). The A-50 accession stood out for the highest mean for morphological characteristics. It may represent a reference in genetic improvement programs to develop cultivars that acquire water and nutrients more efficiently.